Cytological Bone Marrow Cell Differential Counts and Morphologic Findings in Healthy Cynomolgus Monkeys (Macaca fascicularis) from Nonclinical Toxicology Studies. (February 2017) - Carter, Caitlyn M.; Cregar, Laura C.; Aulbach, Adam D.
Cytological bone marrow evaluation is utilized in nonclinical toxicology studies to characterize hematopoietic effects when the combined interpretation of histologic and complete blood count data does not yield sufficient information. Results from cytological bone marrow examination should be interpreted in the context of variability observed in concurrent control animals with consideration of cytologist experience and historical/published data. Cytological bone marrow differential counts and cellular morphologic findings from 130 (66 male, 64 female) healthy control cynomolgus monkeys from nonclinical toxicology studies were retrospectively analyzed. Myeloid to erythroid (M:E) ratios and the percentage of total cells for each cell type were determined from differential cell count data. M:E ratios ranged from 0.6:1 to 2.3:1. Percentages of total granulocytic cells, total erythroid cells, and lymphocytes ranged from 26.6% to 60.6%, 25.7% to 52.2%, and 5.5% to 40.4%, respectively. Monocytes, plasma cells, mast cells, and mitotic figures were typically <1% of total cells. Notable morphologic findings included occasional giant neutrophilic metamyelocytes and band neutrophils, ring-shaped band neutrophil nuclei, metarubricyte nuclear blebbing and binucleation, multiple or nonfused megakaryocyte nuclei, and emperipolesis. These results represent cytological bone marrow findings from healthy control cynomolgus monkeys utilized in nonclinical toxicology studies and provide insight into expected background variability.